Chemotherapy for soft tissue sarcoma. Issue 19 (19th July 2016) - Ratan, Ravin; Patel, Shreyaskumar R.
Abstract : Soft tissue sarcoma is a term used to describe a heterogeneous group of many rare tumors. Since the initial description of activity of doxorubicin, several additional agents have been brought to bear in the treatment of these diseases. Despite 2 recent drug approvals, doxorubicin and ifosfamide remain the most effective chemotherapy drugs available for the treatment of majority of these tumors. Optimal dosing and administration influence outcomes because of the steep dose‐response curves associated with these agents. The debate endures regarding whether patients who have advanced disease should routinely receive single agents sequentially or in combination. Adjuvant therapy remains similarly controversial, although meta‐analyses do support its use. Contemporary treatment of soft tissue sarcoma routinely incorporates additional lines of treatment that have become available over the last 15 years. Fixed‐dose‐rate gemcitabine with or without docetaxel is a standard second‐line treatment. In keeping with the paradigm shift favoring subset‐specific therapy, several recent approvals are linked with specific sarcoma subtypes. Eribulin has recently been approved on the basis of improved overall survival for patients with adipocytic sarcomas, and trabectedin is now approved in the United States for patients with leiomyosarcoma and liposarcoma. Within the spectrum of targeted therapies, pazopanib is approved for all nonadipocytic sarcomas, and imatinib is approved for dermatofibrosarcoma protuberans. Each of these drugs represents incremental rather than radical progress, although they constitute important and much needed treatment options for patients with these diseases. Cancer 2016;122:2952‐2960 . © 2016 American Cancer Society . Abstract : Since the initial description of the activity of doxorubicin, several additional agents have been brought to bear in the treatment of soft tissue sarcomas. These drugs represent incremental rather than radical progress, although they constitute important and much needed treatment options for patients with these rare tumors.